The Classical Arabinogalactan Protein Gene Family of Arabidopsis - Schultz, Carolyn J. (American Society of Plant Physiologists, 2000)
Arabinogalactan proteins (AGPs) are extracellular proteoglycans implicated in plant growth and development. We searched for classical AGPs in Arabidopsis by identifying expressed sequence tags based on the conserved domain structure of the predicted protein backbone. To confirm that these genes encoded bona fide AGPs, we purified native AGPs and then deglycosylated and deblocked them for N-terminal protein sequencing. In total, we identified 15 genes encoding the protein backbones of classical AGPs, including genes for AG peptides—AGPs with very short backbones (10 to 13 amino acid residues). Seven of the AGPs were verified as AGPs by protein sequencing. A gene encoding a putative cell adhesion molecule with AGP-like domains was also identified. This work provides a firm foundation for beginning functional analysis by using a genetic approach.